FOURNIER'S GANGRENE: A CASE REPORT - Morozov, Serhiy; Matvieienko, Mariia; Kozlova, Tetiana (Eastern Ukrainian Medical Journal, 2024)
An increase in the share of patients with purulent-septic processes of soft tissues in surgical hospitals was indicated by statistical and epidemiological data. Currently, it amounts to 28.5%. Over the last decade, the frequency of Fournier's gangrene has increased by 2.2–6.4. This is due to the increase in the number of patients with weakened immunity in the population.Objective. To study the features of the clinical course, diagnosis and treatment of necrotizing fasciitis with progressive tissue necrosis of the genital organs and perineum based on clinical cases.Materials and methods. Three clinical cases of rapidly progressive Fournier's gangrene are described, one of which had a fatal outcome.Results. As a result of complex treatment, which included staged surgical correction, antibacterial therapy, detoxification measures, correction of homeostasis, functions of organs and systems, the condition of patients gradually stabilized: we managed to stop the phenomena of systemic inflammatory reaction, localize the purulent-necrotic process within the affected areas, provide stimulation of reparative processes in the wound. Due to the presence of large tissue defects of the scrotum, two patients underwent surgery. By exposing the testicles and spermatic cords, after cleaning the wounds, the scrotum was reconstructed with the closure of the eviscerated organs with mobilized local tissues, autodermal plastic, secondary sutures for the wound defects of the side wall of the abdomen, inguinal areas, and right thigh. One of the three patients, a 74-year-old man, despite receiving conservative and non-surgical treatment, died on the 9th day as a result of the spread of the purulent-necrotic process and the progression of multiple organ failure.Conclusion. The presented experience of treatment of Fournier's gangrene demonstrates the importance of timely intensive treatment of this severe infectious process, which is accompanied by the rapid destruction of perineal tissues and the spread of the process beyond the affected anatomical area and the development of sepsis with a high probability of death.